Uptake and Outcomes of Sentinel Lymph Node Mapping in Women With Atypical Endometrial Hyperplasia. Issue 5 (May 2021) - Dioun, Shayan; Chen, Ling; Melamed, Alexander; Gockley, Allison; St. Clair, Caryn M.; Hou, June Y.; Tergas, Ana I.; Khoury-Collado, Fady; Hur, Chin; Hershman, Dawn L.; Wright, Jason D.
Abstract : OBJECTIVE: To examine the utilization, morbidity, and cost of sentinel lymph node mapping in women undergoing hysterectomy for complex atypical endometrial hyperplasia. METHODS: Women with complex atypical endometrial hyperplasia who underwent hysterectomy from 2012 to 2018 in the Perspective database were examined. Perioperative morbidity, mortality, and cost were examined based on performance of sentinel lymph node mapping, lymph node dissection or no nodal evaluation. RESULTS: Among 10, 266 women, sentinel lymph node mapping was performed in 620 (6.0%), lymph node dissection in 538 (5.2%), and no lymphatic evaluation in 9, 108 (88.7%). Use of sentinel lymph node mapping increased from 0.8% in 2012 to 14.0% in 2018, and the rate of lymph node dissection rose from 5.7% to 6.4% ( P <.001). In an adjusted model, residence in the western United States, treatment by high-volume hospitals and use of robotic-assisted hysterectomy were associated with sentinel lymph node mapping ( P <.05 for all). The complication rates were similar between the three groups. The median cost for sentinel lymph node mapping (9, 673) and lymph node dissection (9, 754) were higher than in those who did not undergo nodal assessment (8, 435) ( P <.001). CONCLUSION: Performance of sentinel lymph node mapping is increasing rapidly for women with complex atypical endometrial hyperplasia but is not associated with increased perioperative morbidity or mortality. Abstract : Performance of sentinel lymph node mapping is increasing rapidly for women with complex atypical endometrial hyperplasia and is not associated with increased perioperative morbidity or mortality.